Molecular detection of Mycoplasma haemofelis, ‘Candidatus Mycoplasma haemominutum’ and ‘Candidatus Mycoplasma turicensis’ of stray cats residing in Bangkok monasteries, Thailand - Kamyingkird, Ketsarin; Jiyipong, Tawisa; Amavisit, Patamaporn; Stich, Roger W.; Jittapalapong, Sathaporn (Agriculture and Natural Resources, 2021)
Feline hemoplasmosis, an important disease, causes anemia and fatality in felids worldwide. It is caused by the hemotropic bacterial parasites: Mycoplasma haemofelis (Mhf), ‘Candidatus Mycoplasma haemominutum’ (CMhm) and ‘Candidatus Mycoplasma turicensis’ (CMt). In Thailand, many stray cats are frequently seen in monasteries. The current study investigated the infection rate and risk factors associated with hemoplasma infections of stray cats in Bangkok monasteries, Thailand. Polymerase chain reaction was used for detection of Mhf, CMhm and CMt in 1,488 samples from stray cats randomly collected in 50 districts of Bangkok. Risk factors associated with feline hemoplasmosis were also collected and analyzed for correlation with infection. Out of the 1,488 stray cats, 16.1% (239/1,488), 24.5% (365/1,488) and 1.6% (23/1,488) were infected with Mhf, CMhm and CMt, respectively. Mixed infections with two or three hemoplasma species were found in 3.9% (58/1,488) of cats. The risk factor analysis indicated that sex, age, external parasite infestation, environmental conditions and number of cats per monastery were significantly (p < 0.05) associated with feline hemoplasma infections. Feline hemoplasmas were found in 29.4% (129/439) of the monasteries sampled from the 50 districts. In the 29.4% of hemoplasmas-positive monasteries, CMhm (100%), Mhf (96%) and CMt (34%) were identified. The results revealed that feline hemoplasmas were commonly found among stray cats in Bangkok, suggesting the possibility of these animal being a vector for the spread of diseases among outdoor cats.